India: The Golden Jubilee - Granta Publications (London. Penguin Books, 1997)
Over the past two decades India has produced a dazzling variety of new writing in English. 'India Calling' showcases some of this talent, Amit Chaudhuri and Arundhati Roy, alongside contributions from long celebrated writers such as R.K. Narayan, V.S. Naipaul, Nirad Chaudhuri and Ved Mehta.
Keywords: Literature--India